The Monetary System Analysis and New Approaches to Regulation - Serval, Jean-François (The Wiley Finance Series, 2014)
A groundbreaking work that paves the way for a new, pro-active financial system With The Monetary System, innovative author pairing Jean-Francois Serval and Jean-Pascal Tranie devise a comprehensive economic modeling system that accounts for the unprecedented situation facing international and regional economies by developing a controversial new stance on the operation of money in society. Presenting a classification of financial instruments with a view toward their underlying legal structures, the book sheds new light on the present economic and financial problems of slow growth and rising debts, and proposes possible outcomes for the global economy. The authors have already gained international attention with their novel approach to currency, and now they turn their attention to the social function of money in all its myriad forms. The book provides a way forward in an era of increased life expectancy and other new social patterns and the social role of money provides a framework for understanding intergenerational redistribution-an urgently pressing task in our time. New aggregate financial categories and economic modeling reveal a possible foundation for increased financial stability Companion website includes key mathematical models, accounting standards, and PowerPoint slides Comprehensive theoretical underpinning presents the contemporary model of money as a social contract Insights into the current economic situation make sense of sovereign debt risk in markets around the world With questions and answers at the end of each chapter, The Monetary System will help you form a new conception of the role of money in society. Improved regulation and tax policies are needed to stabilize the global economy, and this book provides the framework for getting there